Peningkatan Kinerja Usaha Mikro Melalui Penyusunan Rencana Usaha Dan Laporan Keuangan Pada Kelompok UP2K Kelurahan Gisikdrono, Kecamatan Semarang Barat - Indarto, Indarto; Santoso, Aprih; Santoso, Djoko (Universitas Darussalam Gontor, 2019)
UP2K-PKK is one of the spearheads in the effort to eradicate poverty. This program continues to grow as a poverty reduction program by utilizing the existence of the function of women in the household. One area in Semarang City is very active to move UP2K-PKK is Kelurahan Gisikdrono in West Semarang District. The activities of UP2K-PKK in Gisikdrono currently include 1 special group (poksus) and 10 implementing groups (poklak). The main problem is that the business is still sporadic, not well planned, and they do not know what to do so that business can grow. Besides, business players also complain that they have not been able to determine the cost of their products in a definite manner and have not done well bookkeeping on the business they are doing. Methods of activities in community service this time is in the form of training to the target audience on how to prepare a business plan in terms of market and marketing aspects, technical and operational aspects, aspects of management and organization and financial aspects..The results of community service are: (1) business actors of UP2K group understand the steps to be taken to develop their business through the preparation of business plans from various aspects including; market and marketing aspects, technical aspects, management and organization aspects and financial aspects; and (2) business actors are technically better understanding how to bookkeeping and make good and informative reports on their business.